Measuring intangible cultural heritage: case study of knowledge and practices of Malacca cultural communities - Abu Bakar, Aisyah; Mohamed Osman, Mariana; Bachok, Syahriah; Jaafar, Samsuddin (2013)

(untitled)
This paper reviews methods and implementations of measuring Intangible Cultural Heritage (ICH) in one of the most historical sites in Malaysia, Malacca. Malacca has been declared a World Heritage City on July 7th, 2008 by United Nations Educational, Scientific and Cultural Organization (UNESCO). One of the three selection criterion emphasizes on the ICH expressed in great variety of multicultural activities of the cultured communities in Malacca. Survey Questionnaires have been recently conducted to measure the level of community involvement in cultural activities. Cultural activities refer to cultural expressions adopted in five domains of ICH, namely Oral traditions and expressions, Performing arts; Social practices, Rituals and Festive events; Knowledge and Practices and Traditional craftsmanship. 640 survey forms have been gathered from four locations of residence which are claimed to be the residential areas of cultural communities in Malacca - homes to the Traditional Malays, Portuguese, Chetty, Baba and Nyonya, Indians and Chinese. These locations of residence are Morten Village, Portuguese Village, Heren and Jonker Streets and Gajah Berang Village. This paper provides an analysis of the involvement of the cultural communities in cultural activities of one of the domain of ICH that is Knowledge and Practices concerning Nature and Universe.